Elimination of plasmid pKM101 from Salmonella typhimurium by monoammonium salts - Belicová, A; Ebringer, L; Devínsky, F (Folia microbiologica, 1993)
The frequency of elimination of plasmid pKM101 from Salmonella typhimurium TA92 exposed to the action of 1-alkyl-1-ethylpiperidinium bromides and N-alkyl-N-[5-(benzoyloxy)-3-oxapentyl]-N,N-dimethylammonium bromides was non-linear in the homologous series. Change in the length of the alkyl chain markedly affected the elimination properties of the piperidine derivatives but had no effect on the elimination of benzoyl derivatives. Piperidines exhibited a weaker elimination capacity than the benzoyl derivatives. The most potent eliminator was the octylbenzoyl derivative, which causes the elimination of the plasmid in 80-85% cells.
Keywords: Quaternary Ammonium Compounds; Salmonella typhimurium; soli; plazmidy; kvartérní amoniové sloučeniny; Plasmids; Salts; bromidy; Bromides